LITERASI INFORMASI GURU PENDIDIKAN AGAMA BUDDHA DAN IMPLIKASINYA DALAM PEMBELAJARAN - Suntoro, Suntoro (Universitas Muria Kudus, 2019)
This study aims to describe the information literacy of Buddhist Education teachers in Pati Regency covering aspects of information needs, access to information, and utilization of information in teaching. This study uses a qualitative method. The data collection technique of this study uses interviews, observation, and documentation. Data analysis using the Milles and Hubberman model includes the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of this study include: (1)The information needs of Buddhist Education teachers can be classified into information needs to improve teacher competence and information needs for career advancement; (2) access to information sourced from various locations, the teachers have also been able to analyze, organize, and save information well; (3) the teacher utilizes the information literacy results in teaching and learning activities in the school despite experiencing obstacles such as the lack of infrastructure to support learning.